Circunstanciadores temporais em narrativas escritas - Rocha, Ariana Góes (2018)
Temporal adverb is a label given to the linguistic element that establishes the notion of temporality in texts. Precisely, it refers to temporal conjunctions, adverbs and adverbial locutions of time, with more definite syntactic and semantic specificities, establishing temporal sequencing (MARTELOTTA, 1993). In the narrative text, the temporal adverbs play the role of connectors, since they establish the temporal sequencing of the events that are listed and also function as a strategy of textual cohesion. Considering that there are differences in the use of temporal factors according to the types of text, the degree of formality and the type of record (speech and writing), and that the role of the school is to promote the expansion of the student repertoire, we developed a sequence of activities that culminated in the proposal of a Didactic Module for the treatment of this phenomenon. The activities were developed in the academic period of 2017 with the 7th grade of the Gumercindo Bessa State School, located in the municipality of Estância, state of Sergipe. Initially, we elaborated a diagnostic activity for the production of narratives written from a visual stimulus, in which we could verify that the temporal ordering of the narratives was done mainly by juxtaposition of sentences, and with few uses of temporal adverbs, which, when used, were the closest to speech, such as aí (so), e (and) and então (then) (TAVARES, 1999; BARRETO, FREITAG, 2009). After analyzing the textbook adopted in the class, we found that the treatment given to the temporal adverbs (adverbs and adverbial locutions of time) was not suitable for use, with emphasis on nomenclature. Next, we conducted an investigation of reading and writing habits in the class to identify students' likes and preferences to provide meaningful and motivated learning. Following the guidelines of the National Curriculum Parameters of Portuguese Language (BRASIL, 1998), to contribute to the expansion of the linguistic repertoire of students, based on an approach based on Functionalism of North American and Sociolinguistic, which study linguistic phenomena from of real uses (FURTADO DA CUNHA, TAVARES, 2007; GORSKI; FREITAG, 2007; 2013), we made a didactic module with the objective of working the content of temporal adverbs as a mechanism of textual cohesion in narrative texts. We elaborated a didactic module composed of five activities that stimulate the recognition and use of temporal adverbs. The structure of the teaching material is divided into two stages: theoretical basis on the selected content and the practical section with exercises - two textual productions from visual sequences, two jigsaw puzzles and a text with gaps, as well as elaborated evaluation sheets for the teacher to follow the level of student learning. After the application of the didactic module, we verified in the narratives produced by the students a more diversified repertoire of temporal adverbs, both in quantity and variety, which conferred on the texts written by the students a more formal and more distant character of orality.